👤
Razvanhd287
a fost răspuns

{[-2+(-3)x(-4)-(-5)x(+6)]x(-7):(-8)+9}x10:(-11) va rog dau coroana!

Răspuns :

[tex]\left(-2+\left(-3\right)\left(-4\right)-\left(-5\right)\left(6\right)\right)\frac{-7}{-8}+9\cdot \frac{10}{-11} \\ \\ \left(-2+\left(-3\right)\left(-4\right)-\left(-5\right)\left(6\right)\right)\frac{-7}{-8}=35 \\ \\ 9\cdot \frac{10}{-11}=-\frac{90}{11} \\ \\ Deci \left(-2+\left(-3\right)\left(-4\right)-\left(-5\right)\left(6\right)\right)\frac{-7}{-8}+9\cdot \frac{10}{-11}=35-\frac{90}{11} \\ \\ =\frac{35\cdot \:11}{11}-\frac{90}{11} \\ \\ =\frac{295}{11} \\ \\ [/tex]